Asbestos content of lung tissue in patients with malignant peritoneal mesothelioma: A study of 42 cases. (3rd May 2016) - de Ridder, Gustaaf G.; Kraynie, Alyssa; Pavlisko, Elizabeth N.; Oury, Tim D.; Roggli, Victor L.
ABSTRACT: Lung tissue from 42 peritoneal mesothelioma cases was analyzed by light microscopy and scanning electron microscopy/energy dispersive spectrometry. There were 34 men and 8 women with a mean age of 61 ± 10 years. Also, 17% of cases had histologically confirmed asbestosis, and 26% had only parietal pleural plaques. The asbestos body count exceeded our normal range in 22 of 42 cases (52%). Cases with asbestos-related pulmonary disease had higher fiber burdens than those without. The vast majority of fibers were commercial amphiboles (amosite with lesser amounts of crocidolite). These findings concur with previously published epidemiological observations.